The Dynamics of Motivation and Social Atmosphere of the Classroom in the Process of Pedagogical Intervention of Reading Comprehension - Stranovská, Eva; Szabó, Erzsébet (Journal of Education Culture and Society, 2024)
Aim. The research aim is to investigate the dynamics of motivation and social atmosphere of the classroom under the influence of pedagogical intervention in the reading comprehension process. The partial research aim is to find out the perception of the selected texts and tasks.Methods. Structured observation was used to find out the dynamics of motivation and social atmosphere in the classroom, perception of texts and tasks in the process of pedagogical intervention. The findings were recorded in an observation sheet. Using the research method of qualitative content analysis, it was analyzed how the observed phenomena in the educational process influenced pupils' comprehension. The pedagogical intervention was implemented using the experiment method.Results. Uneven dynamics of motivation were found, i.e., the increase did not occur in a directly proportional way (higher motivation from lesson to lesson), but was influenced by other variables such as the difficulty, interest of texts and tasks. The researchers found an upsurge in pupils' intrinsic motivation to work with a German language text under the influence of the pedagogical intervention. The dynamics of motivation shifted from extrinsic to intrinsic motivation of the pupils. This finding was also supported by the findings on the perception of texts and tasks. In spite of the partial difficulties found in comprehension of texts and tasks to them – difficulty in terms of vocabulary, difficulty in working with literary text, or extensive reading, pupils were intrinsically motivated to work on their comprehension of the text they read. Pupils were found to work little with literary texts in the classroom, resulting in a lack of comprehension of these texts. The dynamics of the social atmosphere in the classroom under the influence of the pedagogical intervention was manifested by a positive and friendly atmosphere and the consequent stimulation of positive affectivity.Conclusion. The research shows that the pedagogical intervention stimulates the dynamics of motivation towards intrinsic motivation, i.e. the usability of texts, the interest to increase the comprehension of texts despite the difficulty of the text and the lower interest in the literary text. Pupils are more interested in factual and usable texts, which they encounter more often in everyday life, and they work with literary tests less frequently. The pedagogical intervention also stimulates the social atmosphere in the classroom towards positive affectivity, which helps to reduce the pupils' emotional filter and promotes the development of reading comprehension skills. A remarkable finding is that the work and attitude of the teacher towards the intervention appears to be a critical factor compared to the effectiveness of the pedagogical intervention. The work and attitude of the teacher towards the intervention can influence to a greater extent the pupils' motivation and the positive atmosphere in the classroom. Regarding the perception of texts and tasks, it should be noted that the complexity or difficulty of texts largely influences the pupils' attitude towards reading comprehension and concentration when working with the text and related tasks. For this reason, it is necessary for the teacher to search for reading texts that are appropriate for each pupil at the same age.